MG-132 interferes with iron cellular homeostasis and alters virulence of bovine herpesvirus 1. (July 2021) - Fiorito, Filomena; Irace, Carlo; Nocera, Francesca Paola; Piccolo, Marialuisa; Ferraro, Maria Grazia; Ciampaglia, Roberto; Tenore, Gian Carlo; Santamaria, Rita; De Martino, Luisa
Abstract: Bovine herpesvirus 1 (BoHV-1) requires an iron-replete cell host to replicate efficiently. BoHV-1 infection provokes an increase in ferritin levels and a decrease of transferrin receptor 1 (TfR-1) expression, ultimately lowering iron pool extent. Thus, cells try to limit iron availability for virus spread. It has been demonstrated that MG-132, a proteasome inhibitor, reduces BoHV-1 release. Since ferritin, the major iron storage protein in mammalian cells, undergoes proteasome-mediated degradation, herein, the influence of MG-132 on iron metabolism during BoHV-1 infection was examined. Following infection in bovine cells (MDBK), MG-132 reduced cell death and viral yield. Western blot analysis showed a significant ferritin accumulation, likely due to the inhibition of its proteasome-mediated degradation pathway. In addition, the concomitant down-regulation of TfR-1 expression, observed during infection, was counteracted by proteasome inhibitor. This trend may be explained by enhanced acidic vesicular organelles, detected by acridine orange staining, determining a reduction of intracellular pH, that promotes new synthesis of TfR-1 degraded in a recycling pathway. In addition, MG-132 influences cellular iron distribution during BoHV-1 infection, as revealed by Perls' Prussian blue staining. However, cellular iron content, evaluated by Atomic Absorption Spectrophotometry, resulted essentially unaltered. These findings reveal that MG-132 may contribute to limit cellular iron availability for virus replication thereby enhancing cell survival. Highlights: To efficiently replicate, Bovine herpesvirus 1 (BoHV-1) requires an iron-replete cell host Proteasome inhibitor MG-132 reduces BoHV-1 release in bovine cells and provokes ferritin accumulation during infection Down-regulation of transferrin receptor 1, observed during BoHV-1 infection, is counteracted by MG-132 MG-132 may contribute to limit cellular iron availability for virus replication thereby enhancing cell survival